Preparation method of anti-icing and de-icing hydrophobic electrothermal graphene coating

Through the combination of hydrophobic treatment and electric heating dual effect of graphene coating, a low-cost electrothermal hydrophobic graphene coating is prepared, solving the problem of high cost and low efficiency of existing anti-icing technology and achieving effective anti-icing on wind turbines Effect.

CN119192971APending Publication Date: 2024-12-27JILIN ELECTRIC POWER RES INST LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411460267.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing anti-icing technology has high cost and low efficiency in industrial applications, especially when wind turbine blades are frozen, resulting in loss of power generation.

Method used

The hydrophobic treatment of graphene coating is adopted, combined with the dual-effect electrothermal and hydrophobic methods, and the combination of graphene, polyurethane resin and nano-SiO2, a low-cost electrothermal hydrophobic graphene coating is prepared to achieve an anti-icing effect.

Benefits of technology

A low-cost electrothermal hydrophobic graphene coating is realized, which improves deicing efficiency, reduces ice adhesion, extends icing time, and meets the needs of deicing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005091669060000021
    Figure FDA0005091669060000021
  • Figure HDA0005091669080000011
    Figure HDA0005091669080000011
  • Figure HDA0005091669080000012
    Figure HDA0005091669080000012
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-icing and de-icing hydrophobic electrothermal graphene coating, which comprises the following steps: preparing conductive slurry taking graphene as a main solute by using DBE as a solvent, and mixing the conductive slurry with waterborne polyurethane resin to prepare a graphene-polyurethane composite coating; and modifying the graphene-polyurethane composite coating by using a nano SiO2 dispersion liquid to finally prepare the electrothermal hydrophobic graphene anti-icing and deicing coating. And a graphene electric heating and hydrophobic coating double-effect mode is combined, so that the anti-icing and de-icing purposes of the blade of the wind driven generator are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an anti-icing and deicing coating, and in particular to a preparation method of an anti-icing and deicing hydrophobic electrothermal graphene coating. Background Art

[0002] Green and clean energy is gaining more and more attention, among which wind energy is valued by the country and enterprises because of its safe, clean and continuous power generation. However, severe icing can cause wind turbines to shut down, reduce the power generation of the generator set, and cause a lot of energy damage. In areas with severe icing, it can cause 20% to 50% power generation damage. In order to solve the problems caused by blade icing, researchers have reported a series of anti-icing technologies. Commonly used methods include surface coating, electric pulse deicing, hot air circulation heating, ultrasonic method, etc. However, these methods have certain limitations in industrial applications.

[0003] In recent years, the deicing idea of ​​combining active deicing with passive deicing has attracted more and more attention from the market, combining the advantages of the two and compensating for each other's shortcomings. For example, the electrothermal super-hydrophobic composite coating can increase the surface temperature by actively generating heat through the coating, inhibit ice crystal formation and prolong the freezing time. The surface of the hydrophobic coating has a low surface energy, which can reduce ice adhesion and improve its deicing efficiency. The disadvantage is that the preparation cost is relatively high. In view of this, the present invention provides a low-cost anti-icing and deicing hydrophobic electrothermal graphene coating. The electrothermal hydrophobic graphene anti-icing coating is obtained by hydrophobic treatment of the graphene coating. The dual-effect mode of graphene electrothermal and hydrophobic coating is combined to achieve the purpose of anti-icing. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing an anti-icing and deicing hydrophobic electrothermal graphene coating. A low-cost electrothermal hydrophobic graphene anti-icing coating is obtained by hydrophobic treatment of the graphene coating. The dual-effect mode of graphene electrothermal and hydrophobic coating is combined to achieve the purpose of anti-icing and deicing.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing an anti-icing and de-icing hydrophobic electrothermal graphene coating comprises the following steps:

[0007] (1) Weigh 1500 g of DBE solvent and 15.2 g of graphene powder and place them in a sample barrel, add 0.152 g of polyvinyl pyrrolidone PVP and 0.304 g of hydroxymethyl cellulose sodium salt CMC according to 1 wt% of the graphene mass, stir the mixed solution with a stirrer for 5 minutes, and then treat it with an emulsifier for 30 minutes to obtain a prefabricated slurry;

[0008] (2) homogenizing the prefabricated slurry twice, obtaining a graphene solute with a certain solid content by suction filtration, adding the graphene solute to the waterborne polyurethane resin so that the graphene concentration is 30%-40%, and mechanically stirring for 1 hour after mixing until the mixture is completely uniform to obtain a conductive slurry;

[0009] (3) Using stainless steel as a substrate, the conductive slurry was coated by manual coating method, and the coating thickness was 0.2 mm. After the film was air-dried for 20 h, it was placed in an oven at 120 ° C for 2 h to obtain a graphene-polyurethane composite coating;

[0010] (4) Dispersing hydrophobic nano-SiO2 particles in an ethanol solution to prepare a dispersion having a nano-SiO2 concentration of 5%-7%, dropping the dispersion on the surface of the graphene-polyurethane composite coating, vibrating, stirring and heating, the nano-SiO2 is adsorbed on the graphene-polyurethane composite coating by electrostatic adsorption, and finally an electrothermal hydrophobic graphene anti-icing coating is obtained.

[0011] Furthermore, the graphene powder in step (1) is prepared by a physical exfoliation method, has 1 to 3 layers, and has a size of 10 μm.

[0012] Furthermore, the graphene concentration in step (2) is 30%.

[0013] Further, the ratio of the graphene solute to the waterborne polyurethane resin in step (2) satisfies the formula Among them, K is the concentration of graphene, m1 is the mass of graphene solute, n is the solid content of graphene, and m2 is the mass of waterborne polyurethane resin.

[0014] Furthermore, in step (2), the solid content of graphene is 4 wt %.

[0015] Furthermore, in step (4), the heating time is 2 hours and the heating temperature is 110°C.

[0016] The present invention can achieve the following beneficial effects:

[0017] By adopting the method of the present invention, a low-cost electrothermal hydrophobic graphene anti-icing coating can be obtained through hydrophobic treatment of the graphene coating, and the dual-effect mode of graphene electrothermal and hydrophobic coating is combined to achieve the purpose of anti-icing and deicing. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Sedimentation test diagram of graphene slurry with different concentrations;

[0019] Figure 2 It is the electrothermal performance curve of graphene-polyurethane composite coating;

[0020] Figure 3The electrothermal performance curve of the electrothermal hydrophobic graphene anti-icing coating. DETAILED DESCRIPTION

[0021] A method for preparing an anti-icing and de-icing hydrophobic electrothermal graphene coating comprises the following steps:

[0022] (1) Weigh 1500 g of DBE solvent and 15.2 g of graphene powder and place them in a sample barrel, add 0.152 g of polyvinyl pyrrolidone PVP and 0.304 g of hydroxymethyl cellulose sodium salt CMC according to 1 wt% of the graphene mass, stir the mixed solution with a stirrer for 5 minutes, and then treat it with an emulsifier for 30 minutes to obtain a prefabricated slurry;

[0023] (2) homogenizing the prefabricated slurry twice, obtaining a graphene solute with a certain solid content by suction filtration, adding the graphene solute to the waterborne polyurethane resin so that the graphene concentration is 30%-40%, and mechanically stirring for 1 hour after mixing until the mixture is completely uniform to obtain a conductive slurry;

[0024] (3) Using stainless steel as a substrate, the conductive slurry was coated by manual coating method, and the coating thickness was 0.2 mm. After the film was air-dried for 20 h, it was placed in an oven at 120 ° C for 2 h to obtain a graphene-polyurethane composite coating;

[0025] (4) Dispersing hydrophobic nano-SiO2 particles in an ethanol solution to prepare a dispersion having a nano-SiO2 concentration of 5%-7%, dropping the dispersion on the surface of the graphene-polyurethane composite coating, vibrating, stirring and heating, the nano-SiO2 is adsorbed on the graphene-polyurethane composite coating by electrostatic adsorption, and finally an electrothermal hydrophobic graphene anti-icing coating is obtained.

[0026] Wherein, the graphene powder in step (1) is prepared by physical exfoliation method, has 1-3 layers and a size of 10 μm;

[0027] In step (2), the solid content of graphene is 4wt%, and the solid content of graphene is determined by stability test. A certain mass of graphene slurry is diluted with deionized water to a content of 0.5, 1, 2, 3 and 4wt%, respectively. Stirring and ultrasonication are performed alternately to fully disperse the graphene slurry in the solution. Figure 1As shown, when the graphene slurry is fully dispersed, the dispersion appears inky black as a whole. However, the appearance of the dispersion does not show changes in the concentration of the solution. The above dispersion was allowed to stand for 24 hours to examine its stability. As shown in the figure, after standing for 24 hours, the 0.5wt% and 1wt% dispersions showed obvious stratification, with the black graphene sheets in the lower half of the dispersion and the upper half clear. The dispersion settled during the standing process, indicating that its stability is poor and it cannot maintain its original dispersion state well. The 2wt%, 3wt% and 4wt% dispersions maintained their initial inky black color without stratification, and no obvious stratification was observed after standing for another 48 hours, proving that their dispersibility is good. Therefore, when preparing the conductive slurry, a graphene solute with a solid content of 4wt% was uniformly selected;

[0028] Among them, the graphene concentration in the conductive slurry is selected to be 30%-40%, which is determined by the electrothermal performance experiment of the graphene-polyurethane composite coating. Stainless steel is used as the substrate, and the conductive slurries with graphene concentrations of 20%, 30% and 40% are coated respectively by an artificial coating method. The coating thickness is 0.2mm. After the film is left to air-dry for 20 hours, it is placed in an oven and baked at 120°C for 2 hours to obtain three specifications of graphene-polyurethane composite coatings. A 10V voltage is applied to the film layers with graphene contents of 20%, 30% and 40%, respectively, for electrothermal performance testing. The specific experimental process is that after the three specifications of the graphene-polyurethane composite coatings are kept warm for half a minute, a 10V voltage is applied to the samples at the same time. Figure 2 It can be seen that the temperature of the film layer with 20% graphene content did not change significantly. The reason is that the graphene content is low and the electrothermal conversion performance is poor. When the graphene content is increased to 30%, the electrothermal performance is significantly improved, and it quickly rises to 130.1°C within 60s, and the maximum temperature can reach 132.6°C, showing excellent electrothermal performance. When the graphene content is increased to 40%, the electrothermal performance is significantly improved. The film layer rises to 145.2°C in only 30s under a voltage of 10V, and the maximum temperature can reach 155.0°C. The application of this film layer for electric heating and deicing is feasible. Considering the comprehensive cost aspect, a graphene concentration of 30% in the conductive slurry is preferred. Therefore, when preparing the conductive slurry, the graphene concentration therein is selected to be 30%;

[0029] Wherein, nano-SiO in the step (4) The concentration of the dispersion liquid is selected 5%-7%, which is determined by the spin coating test experiment, and the hydrophobic nano-SiO of different masses is weighed The particle dispersion is made into a uniform dispersion liquid of 1%, 5%, 7% and 10% in an ethanol solution. The dispersion liquid droplets of the above-mentioned different concentrations are respectively on the glass substrate coated with the PU film, and the spin coating test is carried out. A drop of water is dropped on the film surface formed by the dispersion liquid of different concentrations, when nano-SiO When the dispersion liquid concentration was less (being 1%), the film still presented a hydrophilic state. When nano-SiO When the dispersion liquid concentration was larger (being 5%, 7%, 10%), the nano hydrophobic layer obviously thickened, and the water droplets were dropped on the nano-SiO Film surface, and the nano-SiO Film presented a significant hydrophobic state, but considered that the excessively thick film thickness can cause the heat transfer to be unsmooth, affecting the effect of heating and deicing, and therefore, nano-SiO The concentration of the dispersion liquid is selected 5%-7%.

[0030] Example 1

[0031] Weigh 1500g of DBE solvent and 15.2g of graphene powder and place them in a sample barrel, add 0.152g of polyvinyl pyrrolidone PVP and 0.304g of hydroxymethyl cellulose sodium salt CMC according to 1wt% of the graphene mass, stir the mixed solution with a stirrer for 5 minutes, and then treat it with an emulsifier for 30 minutes to obtain a prefabricated slurry;

[0032] The prefabricated slurry was homogenized twice, and a graphene solute with a graphene solid content of 4% was obtained by suction filtration. The graphene solute was added to 100g of waterborne polyurethane resin to make the graphene concentration 30%. After mixing, the mixture was mechanically stirred for 1 hour until it was completely uniform to obtain a conductive slurry; wherein the mass ratio of the graphene solute to the waterborne polyurethane resin satisfies the formula: Wherein, K is the concentration of graphene (30%), m1 is the mass of graphene solute, n is the solid content of graphene (selected as 4%), and m2 is the mass of waterborne polyurethane resin (100g). The addition amount of graphene solute m1 can be calculated by the formula;

[0033] Using stainless steel as a substrate, a conductive slurry with a graphene concentration of 30% was coated by an artificial coating method, and the coating thickness was 0.2 mm. After the film was air-dried for 20 hours, it was placed in an oven and baked at 120°C for 2 hours to obtain a graphene-polyurethane composite coating.

[0034] Hydrophobic nano-SiO2 particles were dispersed in an ethanol solution to prepare dispersions with nano-SiO2 concentrations of 5% and 7%, respectively. The two dispersions were dropped on the surface of a graphene-polyurethane composite coating with a graphene concentration of 30%, respectively. The solution was vibrated, stirred and heated at 110°C for 2 hours. The nano-SiO2 was adsorbed on the graphene-polyurethane composite coating by electrostatic adsorption, and finally two specifications of electrothermal hydrophobic graphene anti-icing coatings were obtained.

[0035] Figure 3 The electrothermal performance of two kinds of membranes modified by nano-SiO2 dispersion is shown, and compared with the unmodified graphene-polyurethane composite coating with 30% graphene content, it can be seen that the heating rate of the modified membrane has no obvious change, but the maximum temperature has decreased, indicating that the coating of nano-SiO2 has a significant effect on the maximum temperature. The maximum temperature of the membrane modified by 5% SiO2 dispersion is reduced to 94.2℃, and the maximum temperature of the membrane modified by 7% SiO2 dispersion is reduced to 86.7℃. The modification experiment does have a relatively large impact on the electrothermal performance, but it can still meet the requirements of electrothermal deicing. Users can choose the appropriate concentration of nano-SiO2 dispersion for modification according to actual needs.

[0036] The above description is only a preferred specific implementation mode of the present invention. Any equivalent substitutions and modifications made by those skilled in the art without departing from the guidance of the present invention are deemed to fall within the protection scope of the present invention.

Claims

1. A method for preparing an anti-icing and de-icing hydrophobic electrothermal graphene coating, characterized in that , including the following steps: (1) Weigh 1500 g of DBE solvent and 15.2 g of graphene powder and place them in a sample barrel, add 0.152 g of polyvinyl pyrrolidone PVP and 0.304 g of hydroxymethyl cellulose sodium salt CMC according to 1 wt% of the graphene mass, stir the mixed solution with a stirrer for 5 minutes, and then treat it with an emulsifier for 30 minutes to obtain a prefabricated slurry; (2) homogenizing the prefabricated slurry twice, obtaining a graphene solute with a certain solid content by suction filtration, adding the graphene solute to the waterborne polyurethane resin so that the graphene concentration is 30%-40%, and mechanically stirring for 1 hour after mixing until the mixture is completely uniform to obtain a conductive slurry; (3) Using stainless steel as a substrate, the conductive slurry was coated by manual coating method, and the coating thickness was 0.2 mm. After the film was air-dried for 20 hours, it was placed in an oven at 120° C. for 2 hours to obtain a graphene-polyurethane composite coating; (4) Dispersing hydrophobic nano-SiO2 particles in an ethanol solution to prepare a dispersion having a nano-SiO2 concentration of 5%-7%, dropping the dispersion on the surface of the graphene-polyurethane composite coating, vibrating, stirring and heating, the nano-SiO2 is adsorbed on the graphene-polyurethane composite coating by electrostatic adsorption, and finally an electrothermal hydrophobic graphene anti-icing coating is obtained.

2. The method for preparing the anti-icing and de-icing hydrophobic electrothermal graphene coating according to claim 1, characterized in that: The graphene powder in step (1) is prepared by a physical exfoliation method, has 1 to 3 layers and a size of 10 μm.

3. The method for preparing the anti-icing and de-icing hydrophobic electrothermal graphene coating according to claim 1, characterized in that: The graphene concentration in step (2) is 30%. The method for preparing an anti-icing and de-icing hydrophobic electrothermal graphene coating according to claim 1 is characterized in that: in step (2), the ratio of the graphene solute to the aqueous polyurethane resin satisfies the formula Among them, K is the concentration of graphene, m1 is the mass of graphene solute, n is the solid content of graphene, and m2 is the mass of waterborne polyurethane resin.

4. The method for preparing the anti-icing and de-icing hydrophobic electrothermal graphene coating according to claim 1, characterized in that: The solid content of graphene in step (2) is 4wt%.

5. The method for preparing the anti-icing and de-icing hydrophobic electrothermal graphene coating according to claim 1, characterized in that: In step (4), the heating time is 2 h and the heating temperature is 110° C.

Citation Information

Patent Citations

  • Superhydrophobic deicing composite coating and preparation method thereof

    CN110423523A

  • Modified graphene as well as preparation method and application thereof

    CN113429807A

  • Wear-corrosion-resistant super-hydrophobic shape memory alloy coating and preparation method thereof

    CN115044903A